ANALISIS SISTEM INFORMASI AKUNTANSI PEMBELIAN BAHAN BAKU PADA PT. ETERINDO NUSA GRAHA GRESIK - ulum, bustanul; Sulistiowati, Fitriyah (GEMA EKONOMI, 2018)
This study aims to analyze the accounting information system purchasesof raw materials at PT. Eterindo Nussa Graha. The method used isdescriptive research, where this study provides an overview of therelationship between the subjet and the object under study. The subject ofthis research is PT. Eterindo Nusa Graha and the object is the accountinginformation system of raw material cash ingredients. The data used areprimary and secondary data. Data ollection techniques is bydocumentation, observation, and literature study. The results of researchstated that the application of accounting information system purchase ofraw materials that exist in PT. Eterindo Nusa Graha been running welland quite effective. The existence of the concurrent tasks og the financialdepartment in PT Eterindo Nusa Graha also concurentally position in twocompanies at once. DOI : 10.5281/zenodo.3475662